2011
DOI: 10.1002/ajmg.b.31161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a genetic variant of the neuronal growth associated protein Stathmin 1 on cognitive and affective control processes: An event‐related potential study

Abstract: Stathmin 1 (STMN1) is a neuronal growth associated protein (NGAP) that is involved in microtubule dynamics and plays an important role in neurite outgrowth and synaptic plasticity. It is highly expressed in the amygdala, but also in different areas of the neocortex including the frontal lobe. Based on previous findings regarding an impact of STMN1 on fear processing, the present study aimed at extending the evidence concerning its functional role to include the domain of executive (frontal lobe) functions. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 77 publications
0
32
0
1
Order By: Relevance
“…Incorrect trials (i.e. errors or misses) were eliminated and individual reaction times of more than two standard deviations (SD) from a subject's mean were excluded from further analysis (e.g., Dresler et al, 2009;Ehlis et al, 2011). The remaining trials were then averaged for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect trials (i.e. errors or misses) were eliminated and individual reaction times of more than two standard deviations (SD) from a subject's mean were excluded from further analysis (e.g., Dresler et al, 2009;Ehlis et al, 2011). The remaining trials were then averaged for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in stathmin 1 are of interest, as stathmin 1 affects fear responses in mice, 22 and polymorphisms in the stathmin 1 gene have been identified that influence fear and anxiety responses as well as cognitive and affective processing in humans. 53,54 The finding that stathmin 1 is elevated in blast-exposed brain therefore provides a novel target for beginning to understand effects of blast on the brain at the molecular level.…”
Section: Figmentioning
confidence: 99%
“…Thus, it is not surprising that growing evidence links dysfunction in the adult brain to stathmin and microtubules. Stathmin has been implicated in abnormal states of fear, anxiety, cognition, social behavior, and brain trauma in rodents and humans (Brocke et al, 2010; Ehlis et al, 2011; Elder et al, 2012; Martel et al, 2012; Martel et al, 2008; Shumyatsky et al, 2005), suggesting microtubule involvement in these processes. Common single nucleotide polymorphisms (SNPs) in the STMN1 gene significantly impacted fear and anxiety responses in humans, measured with the startle and cortisol stress response (Brocke et al, 2010).…”
Section: Implication Of Stathmin and Microtubule In Neuropsychiatmentioning
confidence: 99%